2011
DOI: 10.3109/10428194.2011.578312
|View full text |Cite
|
Sign up to set email alerts
|

Plerixafor to rescue failing chemotherapy-based stem cell mobilization: it’s not too late

Abstract: Plerixafor can rescue the outcome of failing chemotherapy-based stem cell mobilization. However, the optimal time for plerixafor injection in this setting has not been determined. This was investigated by retrospective analysis of data from 48 mobilizations with plerixafor, chemotherapy, and granulocyte-colony stimulating factor (G-CSF). The required yield of 2.0 × 10(6) CD34+ cells/kg was collected from 71% of patients; the median total yield was 4.1 × 10(6) CD34+ cells/kg. Patients to whom plerixafor was adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
13
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 14 publications
3
13
1
Order By: Relevance
“…The median day of plerixafor injection from chemotherapy was 19 (range, 12-23) vs 15 (range, 12-22) (P ¼ 0.116). These results did not significantly differ and were in line with previous published data, [8][9][10] showing that plerixafor is equally effective at the first and the second mobilization attempt.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…The median day of plerixafor injection from chemotherapy was 19 (range, 12-23) vs 15 (range, 12-22) (P ¼ 0.116). These results did not significantly differ and were in line with previous published data, [8][9][10] showing that plerixafor is equally effective at the first and the second mobilization attempt.…”
supporting
confidence: 92%
“…Preliminary data suggest that the socalled 'plerixafor on demand' based on the peripheral blood (PB) CD34 þ cell count at the time hematopoietic recovery after chemotherapy þ G-CSF may be the most efficient and costeffective use of the drug. [8][9][10] We report our experience with plerixafor 'on demand' after chemotherapy þ G-CSF in lymphoma patients. Our aim was to evaluate the success rate of this strategy, and to define whether the PB CD34 þ cell count monitoring is a reliable method to select patients who merit plerixafor at the first or subsequent mobilization.…”
mentioning
confidence: 99%
“…In some patients, waiting for 1-2 days might abolish the need for plerixafor use especially if the platelet counts are still low. It has been recently shown that when plerixafor is added to chemotherapybased mobilization, it is efficient also after prolonged G-CSF use and with WBC counts exceeding 20×10 9 /l [13]. As, preemptive use of plerixafor after chemomobilization is quite common at least in Europe [6,7,[13][14][15], more experiences are needed in this context to optimize its use.…”
Section: Discussionmentioning
confidence: 99%
“…In all studies, the mobilization regimen was consistent with the regimen that would be used in Ontario clinical practice. Eight of the studies 17,18,[20][21][22][23]26,28 included patients enrolled in a European compassionate-use program (cup) for patients who had previously failed conventional mobilization attempts. The inclusion and exclusion criteria were fully described for all those studies.…”
Section: Literature Searchmentioning
confidence: 99%